1965
DOI: 10.1002/anie.196501521
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dichlorogallane HGaCl2

Abstract: The product is a light-to dark-brown solid depending on its grain size; it is sensitive to moisture and is practically insoluble in all the common organic solvents. In contrast to the nitrosyl chlorides of iron [ l ] and cobalt [2], the new compound cannot be sublimed and is therefore probably polymeric in nature. Its infrared spectrum in Nujol contains N-0 absorptions at 1924 (s), 1761 (vs) cm-1 [3] plus two bands at 309 and 261 cm-1 which can be assigned to V-CI stretching vibrations. Comparison of the infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Toluene and benzene-d 6 were distilled from sodium/benzophenone ketyl under dry dinitrogen. P(SiMe 3 ) 3 The title compound was prepared via the adventitious hydrolysis of a reaction mixture containing P(SiMe 3 ) 3 Table II; selected distances and angles are provided in Table III.…”
Section: Materials and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toluene and benzene-d 6 were distilled from sodium/benzophenone ketyl under dry dinitrogen. P(SiMe 3 ) 3 The title compound was prepared via the adventitious hydrolysis of a reaction mixture containing P(SiMe 3 ) 3 Table II; selected distances and angles are provided in Table III.…”
Section: Materials and Measurementsmentioning
confidence: 99%
“…3 Although a variety 0 of organoindium alkoxides have been fabricated for use in relation to these 0 CMe 3 , 6 CPh 3 , 7 Me, 8 CD 3 , 9 t-Bu' 0 : R = CD 3 ; R' = Me, CD 3 : 9 R = Et; R' = Me, Et 9 R = Bu; R' = Bu, Phnl). The nature of these compounds was established by a combination of NMR spectroscopy, cryoscopic molecular weight determination, and infrared techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrosilanes have long been known to convert chlorogallanes into hydrogallanes at or below room temperature, as according to eq It is likely that residual Et 3 SiH from the synthesis of the silylium ion reagent [Et 3 Si]­[CHB 11 Cl 11 ] caused the formation of an intermediate [H 2 Ga] + ion, which then eliminated H 2 to afford compound 1 .…”
Section: Resultsmentioning
confidence: 99%
“…As this finding was supported by preliminary DFT calculations, which indicated that the Hydrosilanes have long been known to convert chlorogallanes into hydrogallanes at or below room temperature, as according to eq 2. 20…”
Section: Gaclmentioning
confidence: 99%
“…The gallium hydrides are extensively explored within the Group 13 metals hydride chemistry. These compounds attract a significant attention in terms of their practical application and fundamental aspects. For instance, volatile Lewis acid–base adducts of GaH 3 and some related hydridogallium derivatives are considered as potential easy-to-handle sources for preparation of GaN and GaAs films or nanoparticles in MOCVD processes. , Also, dichlorogallane Cl 2 GaH, dialkyl-, and diarylgallanes react with unsaturated substrates (ketones, nitriles, olefins, and alkynes) by addition of the Ga–H bond across the multiple bond to result in hydrogallation products. ,,, Hydrometalation reactions of substituted alkynes by dichloro- or dialkylgallanes have been investigated in detail, and the diversity of the reactions pathways and the frameworks of the formed gallium-containing compounds were shown. , Sometimes, hydrogallation reactions proceed more selectively compared to hydroalumination processes. , …”
Section: Introductionmentioning
confidence: 99%